Influence of occupational safety and health training toward staff practices at fast food restaurant in Malaysia - Sarimah Ismail; Siti Zuhaili Samsudin; Kamisan Pusiran (Institute of Medico-Legal Publications, 2019)
Among food service establishments in Malaysia, fast food restaurant (FFR) was found having zero rate of accident that causes permanent disability and death at workplace. Result of preliminary study of this study showed occupational safety and health training gave high influence to safety and health practices among staff of the FRR. A quantitative research was conducted to identify level of influence of four major areas of the occupational safety and health training (workplace hazards and emergency procedure, personel hygiene and the use of personal protection equipment (PPE), food safety, and cleaning procedure) toward the practices of 225 FRR staff. The staff were selected randomly from various FFRs in Malaysia. Results of the preliminary study indicated overall mean level of influence of those four research variables toward staff practices at workplace was high with mean value=4.35 and standard deviation=0.37. The study suggests for the FFR management to provide future training with holistic content. This study also suggests to Malaysia Ministry of Health to establish guidelines for compulsory on-site similar occupational safety and health training to food handlers in all food service establishments for effective food safety practices as well as for the benefit of public health.